2018
DOI: 10.5194/acp-2018-467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monitoring Global Tropospheric OH Concentrations using Satellite Observations of Atmospheric Methane

Abstract: Abstract. The hydroxyl radical (OH) is the main tropospheric oxidant and is the largest sink for atmospheric methane. The global abundance of OH has been monitored for the past decades with the methyl chloroform (CH3CCl3) proxy. This approach is becoming ineffective as atmospheric CH3CCl3 concentrations decline. Here we propose that satellite observations of atmospheric methane in the shortwave infrared (SWIR) and thermal infrared (TIR) can provide an effective 15 replacement method. The premise is that the at… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Additional constraints on the CH 4 loss rate may also permit a more robust estimate of emissions patterns (5) and assist efforts to assess model O 3 and CH 4 budgets (51). This work is complementary to continuing research into budget-based global OH constraints (23,24). Such methods are inherently subject to uncertainties in emissions and transport; in contrast, our method hinges on our understanding of atmospheric composition and chemistry.…”
Section: Conclusion and Next Stepsmentioning
confidence: 95%
See 1 more Smart Citation
“…Additional constraints on the CH 4 loss rate may also permit a more robust estimate of emissions patterns (5) and assist efforts to assess model O 3 and CH 4 budgets (51). This work is complementary to continuing research into budget-based global OH constraints (23,24). Such methods are inherently subject to uncertainties in emissions and transport; in contrast, our method hinges on our understanding of atmospheric composition and chemistry.…”
Section: Conclusion and Next Stepsmentioning
confidence: 95%
“…Although powerful, MCF-derived OH constraints are also inherently limited in several respects. Declining MCF concentrations presage reduced precision for inferred OH in the coming decade, leading the community to seek alternatives (21)(22)(23)(24). All budget/inversion methods convolute source and sink anomalies, and uncertainties in emissions are not always well known (22).…”
Section: Significancementioning
confidence: 99%
“…The distribution of the methane loss rate due to Cl atoms is shown in Figure 8. The general latitudinal and seasonal patterns are not sufficiently different from OH (shown in Zhang et al, 2018) to allow any effective separation between the two.…”
Section: Atom and Its Impact On Vocsmentioning
confidence: 82%
“…This is a small effect considering the 10% current uncertainty in the overall atmospheric lifetime of methane (Prather et al, 2012). Zhang et al (2018) suggested that satellite observations of the global distribution of atmospheric methane could be used to independently constrain methane sources and the dominant sink from oxidation by tropospheric OH. The distribution of the methane loss rate due to Cl atoms is shown in Figure 8.…”
Section: Atom and Its Impact On Vocsmentioning
confidence: 99%
“…Furthermore, model representations of stratosphere‐troposphere exchange will require improvement, to ensure accurate transport from the upper atmosphere, where 14 CO is produced, to surface observation sites. (iii) CH 4 data themselves can potentially be used to infer [OH] in addition to other terms in the global CH 4 budget, provided that there is high enough spatial density and global coverage in the measurements (Maasakkers et al, ; Y. Zhang et al, ). Such an approach relies on the fact that, compared to observations of lower abundance compounds such as MCF, dense observations of CH 4 are possible from space.…”
Section: Top‐down Source and Sink Estimation At Global And Regional Smentioning
confidence: 99%